“Telling Mathematics”: Storytelling and Counting in Pre-Elementary School - Eugenia Taranto (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2020)
This manuscript is the result of a didactical activity, “Telling mathematics”, elaborated for pupils of Pre-Elementary School in Italy. The aim is to verify if storytelling is a methodology that allows developing approaches to the natural number in a significant way in children belonging to this age group and which mathematical skills are involved when certain processes are stimulated. The manuscript describes the phases in which the teaching experiment was articulated, framed in the Theory of Didactical Situations. In particular, I observe how, thanks to the storytelling, the acquisition of the notion of number in children is conveyed through different approaches to the natural number: cardinal, ordinal, recursive, geometric.